Pemberdayaan Produk UMKM Melalui Kerjasama Dengan Transmart Rungkut Sebagai Upaya Perluasan Pangsa Pasar - Fadilla Mulyasari; Mei Retno Adiwati (Institut Teknologi dan Bisnis Semarang, 2023)
The MSME sector (Micro, Small, Medium Enterprises) makes a large contribution to GDP which reaches 61.07% and contributes to employment absorption of 97% of the total national employment absorption. However, despite the large contribution that has been made, there are still frequent problems with the MSME sector, including the limited quality of human resources, the scope of the market that has not yet been expanded, and management that is not yet modern. Thus, it is necessary to pay attention to the MSME sector so that it is more developed. The purpose of this research is to strengthen competitiveness and expand market share owned by the MSME sector through collaboration with Transmart Rungkut. The method used in this study is descriptive qualitative with data collection techniques through observation conducted at Transmart Rungkut, Surabaya